2017
DOI: 10.1101/205021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Polygenic Risk Scores for Multiple Cancers in a Phenome-wide Study: Results from The Michigan Genomics Initiative

Abstract: Health systems are stewards of patient electronic health record (EHR) data with extraordinarily rich depth and breadth, reflecting thousands of diagnoses and exposures.Measures of genomic variation integrated with EHRs offer a potential strategy to accurately stratify patients for risk profiling and discover new relationships between diagnoses and genomes. The objective of this study was to evaluate whether Polygenic Risk Scores (PRS) for common cancers are associated with multiple phenotypes in a Phenome-wide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
139
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(141 citation statements)
references
References 50 publications
2
139
0
Order By: Relevance
“…Compared to population‐based biobanks, academic medical center‐based biobanks tend to see more patients with rare or complicated diseases due to the availability of specialty care and, thus, are often useful for investigating rare conditions. For example, MGI is enriched for analyses of some cancer types, most notably melanoma of the skin, since Michigan Medicine is known for its skin cancer treatment and care. In all cases, the data generating mechanisms have the potential to induce selection and participation biases into the analysis.…”
Section: Statistical Issues Related To Biobank Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared to population‐based biobanks, academic medical center‐based biobanks tend to see more patients with rare or complicated diseases due to the availability of specialty care and, thus, are often useful for investigating rare conditions. For example, MGI is enriched for analyses of some cancer types, most notably melanoma of the skin, since Michigan Medicine is known for its skin cancer treatment and care. In all cases, the data generating mechanisms have the potential to induce selection and participation biases into the analysis.…”
Section: Statistical Issues Related To Biobank Researchmentioning
confidence: 99%
“…Within pre‐existing biobanks, researchers seek to sample patients for inclusion in a particular study. A common study design involves phenotype‐specific case‐control sampling, where all observed cases for a particular phenotype are selected and some subset of (possibly matched) controls for that phenotype are sampled from the biobank . Cases are often defined as subjects receiving a particular diagnosis code a prespecified number of times, for example, twice.…”
Section: Statistical Issues Related To Biobank Researchmentioning
confidence: 99%
See 3 more Smart Citations